The Effectiveness of Social Assistance Distribution Effectiveness on The Level of Public Satisfaction in Alausalo Village, Gilireng District, Wajo Regency - Yudi Rafial Hadi; Ichsan Kasnul Faraby; Jaya Alam; Husna Fadillah (International Journal of Sustainable Applied Sciences, 2026)
This study examines the effectiveness of social assistance distribution, public satisfaction, and the effect of distribution effectiveness on public satisfaction in Alausalo Village, Gilireng District, Wajo Regency. A quantitative survey was conducted on 51 respondents selected by simple random sampling from 105 beneficiary households. Data were collected through questionnaires, observation, and documentation and analyzed using descriptive statistics, Pearson correlation, determination, and simple linear regression. The results show very good overall scores for both distribution effectiveness and public satisfaction. The correlation coefficient was 0.604, R² was 0.365, and the regression coefficient was 0.584 with p < .001. The findings indicate that more effective distribution is significantly associated with higher public satisfaction and that improving targeting, timeliness, information, and service fairness can strengthen beneficiary satisfaction.